Investigation of the Isolated Cr(VI) Species in Cr/MCM‐41 Catalysts and its Effect on Catalytic Activity for Dehydrogenation of Propane. Issue 23 (7th November 2018) - He, Dedong; Zhang, Yaliu; Yang, Shuang; Mei, Yi; Luo, Yongming
Abstract: Cr‐modified MCM‐41 with different loadings were prepared and tested in the propane dehydrogenation (PDH) reaction. As for Cr/MCM‐41 system, the general knowledge was that high Cr loadings resulted in the reduction of silica surface hydroxyl groups, thus leading to the formation of inactive Cr(III) species, as clusters and/or crystalline Cr2 O3 . However, in the present work, isolated Cr(VI) states were identified in the Cr/MCM‐41 catalysts, instead of Cr(III) species, using UV‐vis and H2 ‐TPR. These isolated Cr(VI) species are difficult to reduce, causing the decreased activity for propane conversion and low selectivity towards C3 H6 in the PDH process. In contrast, a good dispersion of the Cr species was obtained using a chromium column adsorption process, and the absence of the isolated state of Cr(VI) species on this sample contributed to high activity toward PDH process. The investigation of the isolated Cr(VI) species is very important for the Cr‐based PDH catalyst system. Abstract : Caught ! Isolated Cr(VI) states were identified in the Cr/MCM‐41 catalysts used in propane dehydrogenation (PDH) as causing the decreased activity toward propane conversion and low selectivity towards C3 H6 .